Trends in mathematics and science performance in 18 countries: Multiple regression analysis of the cohort effects of TIMSS 1995-2007 - Hong, Hee Kyung (Education Policy Analysis Archives, 2012)
<!– /* Font Definitions */ @font-face font-family:"MS Mincho"; mso-font-alt:"ＭＳ 明朝"; mso-font-charset:128; mso-generic-font-family:modern; mso-font-pitch:fixed; mso-font-signature:-536870145 1791491579 18 0 131231 0; @font-face font-family:Garamond; panose-1:2 2 4 4 3 3 1 1 8 3; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; mso-bidi-font-size:10.0pt; font-family:"Times New Roman"; mso-ascii-font-family:Garamond; mso-fareast-font-family:Garamond; mso-hansi-font-family:Garamond; mso-bidi-font-family:"Times New Roman"; p.Abstract, li.Abstract, div.Abstract mso-style-name:Abstract; margin-top:0in; margin-right:27.35pt; margin-bottom:0in; margin-left:.5in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-ascii-font-family:Garamond; mso-fareast-font-family:"MS Mincho"; mso-hansi-font-family:Garamond; mso-bidi-font-family:"Times New Roman"; letter-spacing:.2pt; @page Section1 size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> The purpose of this study was to simultaneously examine relationships between teacher quality and instructional time and mathematics and science achievement of 8th grade cohorts in 18 advanced and developing economies. In addition, the study examined changes in mathematics and science performance across the two groups of economies over time using data from the TIMSS 1995-2007 assessments. While economy did not account for variation in mathematics and science achievement, findings from regression analyses indicated significant relationships between school inputs and achievement in both groups of countries across the years. Teaching experience was a strong indicator of mathematics performance in developing countries, while instructional time was mildly related to achievement in both subjects in advanced economies.